The impact of digital literacy skills on functional skills in secondary Islamic school teachers: a case study of district Kot Addu, South Pakistan - Majeed, Muhammad Kashif; Tunku Ahmad, Tunku Badariah (Rah-e-Falah Research Center, 2024)
This qualitative assessment explores the effects of adopting digital literacy on the functional ability amongst Islamic secondary school teachers in the District of Kot Addu, South of Pakistan. Realizing the growing role of technology as a part of teaching and learning process the purpose of the research will be to determine the state of digital readiness of these educators and identify possible challenges in using technology in teaching practice and preparing preservice teachers. Through semi structured interviews and focus group discussions data were obtained from a purposive sample of first year teachers across different contexts to understand their experiences and issues encountered. Research outcomes show that there is a moderate digital competence across all participants with evident intention of professional growth hindered by shortage of resources, lack of training opportunities, and organizational culture that is not inclined toward the use of technology. The implications of this study for professional practicum are that professional development should focus on these challenges to support the development of teachers’ competencies related to the use of digital technologies. In conclusion, it is important to state that the studies reiterate the importance of using the Digital Literacy for supporting inclination to relevant and effective teaching learning environment in Islamic education.